The use of certain myths in the work of T.S. Eliot - Hall, Ron F (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1964)
T.S. Eliot's statement that myth is an ordering device in literature 'is constantly belied by his use of myth in his own poems'. This is the belief of the American critic Richard Chase, noted for his work on myths and mythological themes in English and American literature. Whether or not Chase is right must emerge from the chapters which follow. The purpose will be to examine the effects of the use of myths and mythological patterns on Eliot's work in general, rather than to annotate individual mythological allusions. Simply to recognise an allusion is to raise a question, not to answer one: for we have then to decide what the writer hope to achieve by its use, and whether or not he has succeeded. Unless they lead on to such questions, lists of sources contribute little to our understanding of a work. Far more important than incidental allusions are the mythological themes and patterns on the larger scale, which reveal themselves in recurrent allusions and in basic patterns of symbolism. Again, merely to recognise such a pattern is inadequate: in every case a discovery of its function in both the poem's (or play's) structure and the poet's technique should be our main concern. ... Eliot himself has made it clear that in his case the use of myths and mythological patterns has often been a fully conscious, even self-conscious process. Therefore we may apply to his work the questions mention by Norman: what functions the myths fulfil within individual works; and why Eliot uses them in the first place. This last question leads us back to a more fundamental one; why do many writers, especially modern ones, use myths 'in the first place'? The problem involves discussion of the relation between myths and literature and of the nature of myths themselves, this forms the material of the first chapter. The other chapters will deal with some of Eliot's works, attempting to explain and analyse his use of myths in them, and to illustrate its importance in each case.
Keywords: Eliot, T. S. (Thomas Stearns), 1888-1965 -- Knowledge -- Literature; Eliot, T. S. (Thomas Stearns), 1888-1965 -- Criticism and interpretation; Mythology in literature